2011
DOI: 10.1093/hmg/ddr337
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive functional analysis of PTEN mutations: implications in tumor- and autism-related syndromes

Abstract: The PTEN (phosphatase and tensin homolog) phosphatase is unique in mammals in terms of its tumor suppressor activity, exerted by dephosphorylation of the lipid second messenger PIP(3) (phosphatidylinositol 3,4,5-trisphosphate), which activates the phosphoinositide 3-kinase/Akt/mTOR (mammalian target of rapamycin) oncogenic pathway. Loss-of-function mutations in the PTEN gene are frequent in human cancer and in the germline of patients with PTEN hamartoma tumor-related syndromes (PHTSs). In addition, PTEN is mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
166
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(181 citation statements)
references
References 66 publications
15
166
0
Order By: Relevance
“…S7). Next, we used a heterologous assay in which the ability of PTEN to rescue growth of yeast expressing a membrane-targeted mammalian PIK3CA allele (p110α-CAAX) is dependent upon its interaction with the membrane and dephosphorylation of PIP 3 (30)(31)(32). Both the Y240F and Y240E alleles were equally capable of rescuing yeast expressing p110α-CAAX to viability as wild-type PTEN.…”
Section: Phosphorylation Of Tyrosine 240 Does Not Affect the Abilitymentioning
confidence: 99%
“…S7). Next, we used a heterologous assay in which the ability of PTEN to rescue growth of yeast expressing a membrane-targeted mammalian PIK3CA allele (p110α-CAAX) is dependent upon its interaction with the membrane and dephosphorylation of PIP 3 (30)(31)(32). Both the Y240F and Y240E alleles were equally capable of rescuing yeast expressing p110α-CAAX to viability as wild-type PTEN.…”
Section: Phosphorylation Of Tyrosine 240 Does Not Affect the Abilitymentioning
confidence: 99%
“…The total number of variations (676) were sorted into four classes: null (70), autism related (16), somatic cancer associated (502), and germline hamartoma tumor syndrome (PHTS) associated (88). Null variants were derived from dbSNP (Sherry et al, 2001), the Human Gene Mutation Database (HGMD) (Stenson et al, 2014), and variants found to be active in a yeast PI3K/PTEN system (Rodriguez-Escudero et al, 2011;Rodriguez-Escudero et al, 2014). Autism-related variants and variants related to PHTS were derived from the HGMD and other individual publications.…”
Section: Variation Data and Classesmentioning
confidence: 99%
“…Of the cases of autism, at least 70 % have no known genetic mechanisms [16]. The data in the pie chart are hypothetical to reflect a large number of individually rare loci identified in cases; the largest piece of the pie represents a majority of cases in whom a genetic mutation is still not identified phosphatase and tensin homologue protein on chromosome 10 (PTEN) [31,34,35]. Although reports of the exact incidence vary, it is estimated that between 5% and 17% of individuals with autism and macrocephaly carry a PTEN mutation [31,34].…”
Section: Autism With Macrocephalymentioning
confidence: 99%